Implementasi Program Lingkar Refleksi Literasi untuk Siswa Sekolah Dasar - Della Apranita; Deli Wahyuni; Fitrah Rahmadani; Dinda Sriatun; Anisa Turahman (Mataram University, 2026)
Literacy programs in elementary schools tend to focus primarily on reading activities without incorporating reflective processes that can foster students’ critical thinking skills. This study aims to describe the implementation of the Literacy Reflection Circle program based on reflective journals as a strategy to strengthen the critical thinking skills of fourth-grade students at SDN 25 Mataram.This study employed a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. The research subjects consisted of 20 fourth-grade students.The results indicate that the implementation of the Literacy Reflection Circle program enhances students’ engagement in literacy activities, improves their ability to express ideas logically, and increases their confidence in participating in discussions. In addition, students show improvement in understanding, analyzing, and evaluating reading texts.Therefore, this program can serve as an innovative and effective literacy learning model to improve critical thinking skills among elementary school students.